METODA-METODA AKUISISI SISTEM INFORMASI AKUNTANSI BERBASIS KOMPUTER - Nung Harjanto (Wahana: Jurnal Ekonomi, Manajemen dan Akuntansi, 2009)
Every company has its own unique business process compare to its similar industry. That unique business process needs to be supported by Proper Accounting Information System which provides financial information as the basis of decision making. Because the level of business process uniqueness is also different from one company to others, it also needs different Accounting Information System which also has different complexity to support that uniqueness. That difference need of Accounting Information System needs proper method in its acquisition. The method of its acquisition includes bespoke development, purchasing ‘off-the-shelf’ software, end-user-development software, and hybrid approach to system acquisition. Proper method chosen in its acquisition can support the achievement of the efficiency and effectiveness whether in system acquisition itself and its implementation in the company business process.Keywords: accounting information system, financial information, system acquisition methods